Mindfulness, Education, and Exercise for age-related cognitive decline: Study protocol, pilot study results, and description of the baseline sample. (October 2020) - Wetherell, Julie Loebach; Ripperger, Hayley S; Voegtle, Michelle; Ances, Beau M; Balota, David; Bower, Emily S; Depp, Colin; Eyler, Lisa; Foster, Erin R; Head, Denise; Hershey, Tamara; Hickman, Steven; et al.
Background/Aims: Age-related cognitive decline is a pervasive problem in our aging population. To date, no pharmacological treatments to halt or reverse cognitive decline are available. Behavioral interventions, such as physical exercise and Mindfulness-Based Stress Reduction, may reduce or reverse cognitive decline, but rigorously designed randomized controlled trials are needed to test the efficacy of such interventions. Methods: Here, we describe the design of the Mindfulness, Education, and Exercise study, an 18-month randomized controlled trial that will assess the effect of two interventions—mindfulness training plus moderate-to-vigorous intensity exercise or moderate-to-vigorous intensity exercise alone—compared with a health education control group on cognitive function in older adults. An extensive battery of biobehavioral assessments will be used to understand the mechanisms of cognitive remediation, by using structural and resting state functional magnetic resonance imaging, insulin sensitivity, inflammation, and metabolic and behavioral assessments. Results: We provide the results from a preliminary study (n = 29) of non-randomized pilot participants who received both the exercise and Mindfulness-Based Stress Reduction interventions. We also provide details on the recruitment and baseline characteristics of the randomized controlled trial sample (n = 585). Conclusion: When complete, the Mindfulness, Education, and Exercise study will inform the research community on the efficacy of these widely available interventions improve cognitive functioning in older adults.